2020
DOI: 10.1111/saje.12262
|View full text |Cite
|
Sign up to set email alerts
|

Spillovers of the Conventional and Unconventional Monetary Policy from the US to South Africa

Abstract: This paper assesses the effect of US monetary policy on South Africa during the period 1990-2018. We separately analyse and compare the effect of conventional monetary policy, before the Global Financial Crisis, and unconventional monetary policy, after the US monetary policy reached the zerolower bound. Our impulse response function results indicate that monetary policy in South Africa is somewhat independent, responding to local inflation, economic activity and financial conditions. However, the variance dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The study by (Hoek et al, 2022) discovered that the United States' interest rate policy disrupted the economic progress of developing countries. Similar findings were produced by (Aizenman et al, 2020;Kabundi et al, 2020;Kolasa and Wesołowski, 2020;MacDonald and Popiel, 2020;Trung, 2019), which demonstrated that the US Tapering off policy caused financial spillovers to economic growth in emerging nations. According to the study (Georgiadis and Schumann, 2021), the United States' change in export and import caused spillover effects.…”
Section: Introductionsupporting
confidence: 70%
“…The study by (Hoek et al, 2022) discovered that the United States' interest rate policy disrupted the economic progress of developing countries. Similar findings were produced by (Aizenman et al, 2020;Kabundi et al, 2020;Kolasa and Wesołowski, 2020;MacDonald and Popiel, 2020;Trung, 2019), which demonstrated that the US Tapering off policy caused financial spillovers to economic growth in emerging nations. According to the study (Georgiadis and Schumann, 2021), the United States' change in export and import caused spillover effects.…”
Section: Introductionsupporting
confidence: 70%
“…Dedola et al and Degasperi et al studied 36 and 30 foreign economies respectively, and concluded that output and industrial production in both developed and emerging economies would decline after the tight US monetary policy [1,2]. Some researches, however, revealed the diverse responses of output in OECD countries [3], or even the different responses of output in the same country to conventional and unconventional expansionary US monetary policy [4]. Yet Willems argued that US monetary policy had no significant impact on the output of dollarized countries [5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The impulse responses are calculated using a medium scale Bayesian VAR model as in Kabundi et al (2020). The model consists of 20 variables.…”
Section: Monetary Policy and Credit Conditionsmentioning
confidence: 99%